Leibnitz. - Bibliographisches Institut (Hildburghausen) (Hildburghausen : Bibliographisches Institut in Hildburghausen, 1850)
Portret muškarca.
Dolje sredina ispod prikaza otisnuto: LEIBNITZ // EIGENTHUM & VERLAG DES BIBL. INSTITUTS IN HILDBURGHAUSEN.
Digitalna reprodukcija
Keywords: Nadorezi; Portreti